Pembentukan Sikap Tawadhu’ dan Ta’awun Melalui Metode Role Playing pada Mata Pelajaran Al-Qur’an Hadis di MI Islamiyah Genggong Jogorogo Ngawi - Elliya Nafilatul Afifah; Moh. Asvin Abdurrahman; Samsudin Samsudin (BASICA, 2025)
This study aims to analyze the implementation of the role playing method in shaping tawadhu' (humility) and ta'awun (mutual assistance) attitudes in Al-Qur'an Hadith learning at MI Islamiyah Genggong Jogorogo Ngawi. The background of this research is the gap between Islamic character values taught and their implementation in students' daily lives. The research method uses a qualitative descriptive approach with data collection techniques including interviews, observation, and documentation. Data validity is tested through technical triangulation, while data analysis follows the Miles & Huberman model consisting of data reduction, data presentation, and conclusion drawing. The research results show that: (1) The application of the role playing method in shaping tawadhu' attitudes is carried out through three learning stages: pre-instructional, instructional, and evaluation stages, forming tawadhu' attitudes towards teachers and fellow students; (2) The application of the role playing method in shaping ta'awun attitudes pays attention to three principles: role taking, role making, and role negotiation, based on the concepts of ta'awun in virtue, loyalty among Muslims, ittihad efforts, and avoiding hostility; (3) The implications are shown through attitudes of respecting teachers, working together in group tasks, helping friends sincerely, visiting sick friends, and mediating conflicts between friends. This research contributes to the development of active and interactive learning methods in Islamic character education at the elementary level.